2010
DOI: 10.1016/j.jtbi.2010.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Holling type III zooplankton functional response: Bringing together field evidence and mathematical modelling

Abstract: Food-web population models are rather sensitive to parameterization of functional response in predation terms. Theoretical studies would predict enhancing of ecosystems' stability for a functional response of sigmoid type (Holling type III). The choice of a correct type of response is especially important for modelling outcome of grazing control of algal blooms by zooplankton in nutrient-rich ecosystems. Extensive experiments on zooplankton feeding in laboratories show non-sigmoid nature of response for most h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 59 publications
3
59
0
Order By: Relevance
“…The zooplankton parameters were designed for the CCS by comparison with other planktonic model studies [29], [33], [34], [35]. We also used a Holling type III formulation for grazing, which is numerically more stable than the default Ivlev formulation used commonly in NEMURO ([36], [37], and references therein). Note that Li et al [32] compared Ivlev and Holling type III grazing formulations in the CCS and showed that they gave statistically indistinguishable results.…”
Section: Methodsmentioning
confidence: 99%
“…The zooplankton parameters were designed for the CCS by comparison with other planktonic model studies [29], [33], [34], [35]. We also used a Holling type III formulation for grazing, which is numerically more stable than the default Ivlev formulation used commonly in NEMURO ([36], [37], and references therein). Note that Li et al [32] compared Ivlev and Holling type III grazing formulations in the CCS and showed that they gave statistically indistinguishable results.…”
Section: Methodsmentioning
confidence: 99%
“…According to Real (1977), we use a modified Michaelis-Menten equation to describe the feeding response (ingestion) to food availability. Given opposed perspectives about the correct form for the functional response applied to zooplankton as summarized in Morozov (2010), we adopted the sigmoidal shape (Holling type III, Holling, 1959). In context of multiple prey resources, the review of Gentleman et al (2003) showed that some commonly used formulations exhibit anomalous dynamics such as negative switching and sub-optimal feeding.…”
Section: Model Closures: Detritus and Heterotrophsmentioning
confidence: 99%
“…A turbulent environment would disturb the predator, making it harder or even unnecessary to behave like this because the turbulent medium force the plankton to some random motion. Morozov (2010) showed that the sigmoid grazing function (Holling-type III) is realistic for heterogeneous prey distributions while in a well mixed homogeneous environment the predators' behavior has to be described less sigmoid (Holling-type I or II). Therefore we model the change in the predators behavior by changing from a Holling-type III functional response in a nonturbulent environment, to Holling-type II in a strongly turbulent, and therefore well mixed, environment.…”
Section: General Biological Modelmentioning
confidence: 99%